+0  
 
0
33
1
avatar

9a2-m2+10mn-25n2

 

 

 

pliiiiiiz help

Guest Sep 7, 2017
Sort: 

1+0 Answers

 #1
avatar+90136 
+1

9a2-m2+10mn-25n2

 

\(9a^2-m^2+10mn-25n^2\\ =9a^2-[m^2-10mn+25n^2]\\ =9a^2-(m-5n)^2\\ =[3a-(m-5n)][3a+(m-5n)]\\ =(3a-m+5n)(3a+m-5n)\\\)

Melody  Sep 7, 2017

26 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details